Effects of Dialogue Journal Writing and Quickwriting on Language Anxiety and Writing Performance - Yahya, Saroya (2004)
The purpose of this study is to compare the effects of dialogue journal writing to that of quickwriting in the teaching and learning of the English language. The effects of the treatments on language anxiety and writing performance were assessed. This ten week quasi-experimental study involved 96 matriculation college students. Data was derived from questionnaires and writing performance test administered prior to and after the treatments. Descriptive statistics, ANCOVA and t-test were employed to analyse the data. The findings of the study revealed that dialogue journal writing group's performance on language anxiety and writing showed significant improvement than that of the quickwriting group. Significant differences between the two groups in terms of communication apprehension and fear of negative evaluation levels were also noted. In addition, the dialogue journal writing group was also seen to have significantly higher scores in the writing assessment categories namely content, organization, language use, vocabulary and mechanics compared to that of the quickwriting group. In sum, dialogue journal writing showed favourable effects on language anxiety and writing performance. The findings of the present study were in accordance with theoretical assumptions of dialogue journal writing, language anxiety and writing performance. The results provided support for the view that dialogue journal writing has the potential to bring about a non-threatening language-learning atmosphere necessary to reduce language anxiety and improve writing performance. The implication of the study suggests that dialogue journal writing could be beneficial in lowering language anxiety and improving writing quality in the second language classroom